A conexão homem/camarão (Macrobrachium carcinus e M. acanthurus) no Baixo São Francisco alagoano: uma abordagem etnoecológica - Montenegro, Sineide Correia Silva (2002)
The main objective of this research was to characterize and interpret the relationship of Man/shhmp in the lower São Francisco river in the state of Alagoas by means of studies about the ethnobioiogic and ethnoecologic knowledge of fishermen about "pitu" {Macrobrachium carcinus) and about "shrimp" (Aí. acanthurus) from the communities of Piranhas, Traipu and Penedinho. The fishing of "pitu" which occurs from the Piranhas till the mouth of the river, represents a good percentage of the income of fishermen from lower São Francisco river, specially of the fishermen from the municipality of Piranhas. In the same way, the fishing of "shrimp" (Aí. acanthurus) is also responsible for the revenue of many famiiies of fishermen from the municipalities of Traipu and Piaçabuçu, specially from Penedinho. In the last years, the shortage of these resources has brought a social problem, whose aggravation becomes a growing challenge to the construction of a future to the fishing in the region. To research the relationship of Man/shrimp in the lower São Francisco river in the state of Alagoas using ethnoecological as well as ecologic analysis, has at least two fundamental objectives: (a) to understand how the fishermen populations from "pitu" and "shrimp" are integrated in the informational netof the ecossystem; (b) integrate, by means of appreciation of their knowledge, the knowledge about classification, fishing and control, in searrch of alternatives for the management and environment planning. To integrate the knowledge of fisherment to those brought about by science, the analysis of these dada was directed by complex thoughts, whose essence is the integration of knowledges as a multidimensional and unseparable phenomenon at the same time. This way, the cultural data collected through the techniques used by social sciences (testimonies, oral statements) were integrated to the biological methods in an attempt to understand the processes of interaction which these communities of fishermen have with the environment. Chapter 4 deals with the ethnobiological knowledge with special attention in the identification of ecological criteria used in the classification of shrimps, beyond understanding their language and logic underlying the knowledge of the natural world. Chapter 5 discusses the fishing, the strategies and it's conective bases revealing how the fishermen populations connected in the past and connected nowadays with the vegetables, the minerais and with themselves. The construction of the hydroelectric power station of Xingó is affecting and transforming the territory of waters, and with this, the space of material and social reproduction and fishermen. To understand the re-organizing promoted by these transformations, chapter 6 shows how fishermen from "pitu" of Entremontes, occupy the fishing spaces, and discuss their territoriality, which may serve as aid for the implantation of a participative administration. As the barrages of the river directly affect the reproduction of species, Chapter 7 deals with reproductive strategis of "pitu" in areas nearby and distant from the barrage of Xingó incorporating hypothesis about the reproductive cycle of this specie, elaborated from the knowledge of fishermen of Piranhas. The oral history of fishermen allows us to know the cultural and biological changes brought about in the fishing in different times. For implanting the policy of participative administration, it is important that the knowledge about the environment and informal rules Consolidated between fishermen be taken into account.